2018
DOI: 10.15191/nwajom.2018.0603
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Human Side of Meteorology: A Brief Report on the Psychology of Meteorologists

Abstract: : Exploring the human side of meteorology: a brief report on the psychology of meteorologists. J. Operational Meteor., 6 (3), 23-32, doi: https://doi.org/10.15191/nwajom.2018 Links between autism spectrum conditions and scientific aptitude were first investigated twenty years ago. Since then, associations between autism and STEM (science, technology, engineering, and math) aptitude have been established and discussed via the empathizing-systemizing (E-S) theory. E-S theory hypothesizes that autistic individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…However, meteorologists who gravitate towards weather broadcasting are much more extroverted (Bolton and Ault 2019), sharing this trait with social scientists (Feist 2006). This is in line with the hybrid cognitive profile hypothesis (Baron-Cohen 2003) and results in support of this, indicating meteorologists are strong in empathizing as well as systemizing (Bolton et al 2018a). Second, and on a related note, these individuals will likely be strong in systemizing with a correspondingly higher interest for things than for people (Feist 2006;Graziano et al 2011;Prediger 1982).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…However, meteorologists who gravitate towards weather broadcasting are much more extroverted (Bolton and Ault 2019), sharing this trait with social scientists (Feist 2006). This is in line with the hybrid cognitive profile hypothesis (Baron-Cohen 2003) and results in support of this, indicating meteorologists are strong in empathizing as well as systemizing (Bolton et al 2018a). Second, and on a related note, these individuals will likely be strong in systemizing with a correspondingly higher interest for things than for people (Feist 2006;Graziano et al 2011;Prediger 1982).…”
Section: Discussionsupporting
confidence: 72%
“…Third, one might expect weather-interested students to display higher levels of trait conscientiousness, and thus to have a higher regard for duty and commitment; and to be more dispositionally open to new experiences. Our work with meteorologists (Bolton et al 2018a; Bolton and Ault 2019) has found them highly conscientious, agreeable, and extraverted (regarding this and empathy, they seem to present a hybrid cognitive profile among physical scientists). Feist (2012) found openness and NFC positively correlated with one another and that introversion is likewise linked with science interest.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Like geologists, operational meteorologists regularly perform cognitively complicated tasks that involve analyzing data from satellite images, radar, and remote sensors, while digesting output from numerical model guidance. Human performance studies in meteorology have exposed revelatory and practical insights about operational meteorology, such as decision making (Joslyn and Jones 2008;Wilson et al 2016), mental health (Bolton et al 2018), color salience and interpretation of displays (Bryant et al 2014), factors of workstation design (Hoffman 1991), and forecaster use of mental models (Trafton et al 2000). However, the way that specific cognitive factors affect performance of meteorological tasks is an under-investigated area, yet one that may yield insight into how to best train and educate operational meteorologists.…”
Section: Introductionmentioning
confidence: 99%